Evaluation of the Performance of Dams and Irrigation Networks in the Kalibumi Irrigation Area in Nabire Regency - Maria Joy Waroi; Mujiati Mujiati; Harmonis Rante; Bernathius Julison; Duha Awaluddin; Dewi Ana Rusim (Publikasi Indonesia, 2024)
Development of irrigation district (DI) in Nabire district began from 1972/1973 until 2014 the government carried out is 6400 ha. The purpose of this study is to eval_uate the performance of the wells and networks of the irrigation areas of the calibumi. The results of this study are known that the performance of Nabire's wells and irrigation networks that have been awakened is still in low performance and require attention with the overall value of 64.74% consisting of the performance value of the physical Prasarana 24.34%, plant productivity 9.86%, the supporting networks 3.33%, the Organization of Personnel 9.18%, Documentation 2.74% and P3A/GP3A / IP3A 5.37% This indicates that the existing operating and maintenance system is still very poorly in accordance with the Regulation of the Minister of Public Works and People's Housing No. 12/PRT/M/2015 on the Exploitation and Maintenance of Irrigation Networks as assessed using the e-PAKSI application.